Culture Change and Affectionate Communication in China and the United States: Evidence From Google Digitized Books 1960–2008 - Wu, Michael Shengtao; Li, Boyuan; Zhu, Liangliang; Zhou, Chan (Frontiers in Psychology, 2019)
Humans are born with the ability and the need for affection, but communicating affection as a social behavior is historically bound. Based on the digitized books of Google Ngram Viewer from 1960 through 2008, the present research investigated affectionate communication (AC) in China and the United States, and its changing landscape along with social changes from collectivist to individualistic environments. In particular, we analyzed the frequency in terms of verbal affection (e.g., love you, like you), non-verbal affection (e.g., hug, kiss), and individualism (indicated by the use of first-person singular pronouns such as I, me, and myself) in Chinese and American books. The results revealed an increasing trend for AC in recent decades, although the frequency of affection words was lower in Chinese than in American books. Further, individualism was positively related to the frequency of affection words in both Chinese and American books. These results demonstrate the effect of cultural changes on AC, in that affection exchange becomes popular in adaptation to individualistic urban environments. These findings exemplify a cross-cultural difference in the expression of love and the cultural universality of social change in Eastern and Western societies.